Dampak Konferensi Internasional “Infinity Experience of Nature and Sport tourism” Terhadap Pengembangan Sport Tourism Kawasan Ekonomi Khusus Mandalika - Lalu Syafril Rahmadio (Politeknik Pariwisata NHI Bandung, 2022)
Mandalika area is special place with beautiful nature and local wisdom, it gives different experience for tourist. Tourism sector is foreign exchange earner beside oil-gas sector. In 2019, tourism sector contributed foreign exchange of 229,50 trillion rupiah. However, with the pandemic Covid-19, tourism sector in Mandalika experienced a sharp decline. Various efforts were made by the local government to revive tourism sector in Mandalika during pandemic, including by making sport tourism a new icon of Mandalika tourism. Development of international circuit Mandalika also strengthen the branding of “Mandalika Experience” to attract more foreign tourists to come to Mandalika. This study aims to explore the impact of sport tourism development in Mandalika in taking the target market and forming a market tourist who are interested in sport tourism activities. Analysis method in this study using descriptive qualitative method which obtained from secondary data from social media and online news portal. The result of this study shows that the impact of sport tourism theme that revive tourism sector in Mandalika is very positive. There is an increase in tourist arrivals during World Superbike Championship event, but there are still many evaluations that must be improved so that international events that will be held in the future will can increasing the NTB local economy.